Quality control in podiatry radiology: proposed criteria for image quality and reference dose - González, Luciano; Becerro de Bengoa, Ricardo; Moro, Javier (Revista Internacional de Ciencias Podológicas, 2011)
Spanish legislation transposing the Community legislation on the quality of radiological acts obliges holders of diagnostic radiology facilities to follow a quality assurance program. The program should cover both aspects of radiation protection of patients and quality of the image obtained. This work aims to facilitate the achievement of these goals in podiatric consultation. To this goal, quality criteria based on anatomical findings are proposed for the most usual podiatric X–ray projections, and a provisional reference dose value for the dorso–plantar projection of 2,2 mGy is also proposed.
Keywords: Podiatric radiography; Quality control; Dosimetry; Image quality